2019
DOI: 10.1002/jcp.29218
|View full text |Cite
|
Sign up to set email alerts
|

Organic anion transporters and PI3K–AKT–mTOR pathway mediate the synergistic anticancer effect of pemetrexed and rhein

Abstract: The aim of this study was to explore whether rhein could enhance the effects of pemetrexed (PTX) on the therapy of non-small-cell lung cancer (NSCLC) and to clarify the associated molecular mechanism. Our study shows that rhein in combination with PTX could obviously increase the systemic exposure of PTX in rats, which would be mediated by the inhibition of organic anion transporters (OATs). Furthermore, the toxicity of PTX was significantly raised by rhein in A549 cells in a concentration-dependent manner.Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…In vitro Caco-2 p-ERK1/2↑ (at higher concentrations of rhein) [150] In vitro HT29, HCT116, Colo205, SW620 HIF-1α↓, PD-L1↓, VEGF↓, COX-2↓, galectin-1↓ [98] In vitro HCT116, SW620 p-STAT3↓ [151] Glioma In vitro F98 ERK1/2↓ [152] In vitro T98G, U87, U251 Ac-K100↑, NDRG1↑ [153] Leukemia In vivo EU-1 injected SCID mice MDM2↓, p53↑ [154] In vitro HL-60 Cleaved caspase↑, cleaved PARP↑, cleaved Bid↑, ∆Ψm↓ [145] In vitro NB4 p-ERK↑, Caspase-3↑ [155] Liver cancer In vitro and in vivo HepG2, HepG2 injected BALB/c-nu mice β-catenin↓, S phase arrest↑ [111] In vitro HepG2 CD95↑, p53↑, p21/WAF↑, mCD95L↑, sCD95L↑ [96] In vitro BEL-7402 c-Myc↓, Caspase-3↑, S phase arrest↑ [54] In vitro SMMC-7721, SMMC-7721/DOX ATP synthesis↓, inner ∆Ψm↓ [156] In vitro HepG2, Huh7 ROS↑, p-c-Jun↑, Caspase-3↑ [55] Lung cancer In vitro and in vivo PC-9, H460, A549, H460 xenograft mice STAT3↓, Bax↑, Bcl-2↓, G2/M phase arrest↑ [157] In vitro A549 p-PI3K↓, Akt↓, mTOR↓, Bcl-2↓ [158] In vitro A549 G0/G1 phase arrest↑, GADD153↑, GRP78↑, Cyt c↑,…”
Section: Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro Caco-2 p-ERK1/2↑ (at higher concentrations of rhein) [150] In vitro HT29, HCT116, Colo205, SW620 HIF-1α↓, PD-L1↓, VEGF↓, COX-2↓, galectin-1↓ [98] In vitro HCT116, SW620 p-STAT3↓ [151] Glioma In vitro F98 ERK1/2↓ [152] In vitro T98G, U87, U251 Ac-K100↑, NDRG1↑ [153] Leukemia In vivo EU-1 injected SCID mice MDM2↓, p53↑ [154] In vitro HL-60 Cleaved caspase↑, cleaved PARP↑, cleaved Bid↑, ∆Ψm↓ [145] In vitro NB4 p-ERK↑, Caspase-3↑ [155] Liver cancer In vitro and in vivo HepG2, HepG2 injected BALB/c-nu mice β-catenin↓, S phase arrest↑ [111] In vitro HepG2 CD95↑, p53↑, p21/WAF↑, mCD95L↑, sCD95L↑ [96] In vitro BEL-7402 c-Myc↓, Caspase-3↑, S phase arrest↑ [54] In vitro SMMC-7721, SMMC-7721/DOX ATP synthesis↓, inner ∆Ψm↓ [156] In vitro HepG2, Huh7 ROS↑, p-c-Jun↑, Caspase-3↑ [55] Lung cancer In vitro and in vivo PC-9, H460, A549, H460 xenograft mice STAT3↓, Bax↑, Bcl-2↓, G2/M phase arrest↑ [157] In vitro A549 p-PI3K↓, Akt↓, mTOR↓, Bcl-2↓ [158] In vitro A549 G0/G1 phase arrest↑, GADD153↑, GRP78↑, Cyt c↑,…”
Section: Colon Cancermentioning
confidence: 99%
“…Many reports have also highlighted the potential therapeutic effects of rhein against lung cancer. Bu et al (2020) demonstrated that rhein induced apoptosis in A549 cells by modulating the expression of p-AMPK, mTOR, and Bcl-2 proteins [158]. The reduced Bcl-2 expression, Cyt c efflux, the rapid loss of ∆Ψm and enhanced caspase-3 activity led to apoptosis in these cells.…”
Section: Lung Cancermentioning
confidence: 99%
“…Rhein is found in R. palmatum L., Aloe barbadensis Miller, Cassia angustifolia Vahl and P. multiflorum Thunb, [ 77 ] which has anti‐inflammatory, [ 78 ] anti‐cancer, [ 79 ] antioxidant [ 80 ] and neuroprotection activities. [ 81 ] Rhein could improve recognition memory impairment, alleviate neuroinflammation and BDNF deficits in the perirhinal cortex on high‐fat‐diet‐induced animal model.…”
Section: Quinones and Its Role In Admentioning
confidence: 99%
“…It was reported to attenuate both innate and adaptive immune responses, and inhibit in ammatory cell recruitment and oxidative stress as well [15,32]. Rhein a major component of many medicinal herbs with various properties, including anti-in ammatory, antioxidant and anticancer activities [33][34][35]. Oxidative stress has been observed in the onset and progression of cataractogenesis [36,37], and antioxidants and free radical scavengers have been suggested as potential drugs for the management of cataracts.…”
Section: Discussionmentioning
confidence: 99%